Editorial Board (PLA Inside Out: An International Journal on Theory, Research and Practice in Prior Learning Assessment, 2026)
Editorial BoardCarl Burkart (Co-Editor)Deb Carr (Guest Editor)Alexa Collesides (Editorial Team Member)Ruud Duvekot (Co-Editor)Susan Forseille (Co-Editor)Amy Giaculli (Associate Editor)Alan Mandell (Founding Co-Editor)Nan Travers (Founding Co-Editor)Don Presant (Guest Editor)Serge Ravet (Guest Editor)